In-hospital mortality of patients with acute coronary syndrome (ACS) after implementation of national health insurance (NHI) in Indonesia - Nurul Qalby; Dian S. Arsyad; Andriany Qanitha; Maarten J. Cramer; Yolande Appelman; Dara R. Pabittei; Pieter A. Doevendans; Idar Mappangara; Akhtar Fajar Muzakkir (BMC Health Services Research, 2024)
Abstract Background The National Health Insurance (NHI) was implemented in Indonesia in 2014, and cardiovascular diseases are one of the diseases that have overburdened the healthcare system. However, data concerning the relationship between NHI and cardiovascular healthcare in Indonesia are scarce. We aimed to describe changes in cardiovascular healthcare after the implementation of the NHI while determining whether the implementation of the NHI is related to the in-hospital mortality of patients with acute coronary syndrome (ACS). Methods This is a retrospective comparative study of two cohorts in which we compared the data of 364 patients with ACS from 2013 to 2014 (Cohort 1), before and early after NHI implementation, with those of 1142 patients with ACS from 2018 to 2020 (Cohort 2), four years after NHI initiation, at a tertiary cardiac center in Makassar, Indonesia. We analyzed the differences between both cohorts using chi-square test and Mann-Whitney U test. To determine the association between NHI and in-hospital mortality, we conducted multivariable logistic regression analysis. Results We observed an increase in NHI users (20.1% to 95.6%, p < 0.001) accompanied by a more than threefold increase in patients with ACS admitted to the hospital in Cohort 2 (from 364 to 1142, p < 0.001). More patients with ACS received invasive treatment in Cohort 2, with both thrombolysis and percutaneous coronary intervention (PCI) rates increasing more than twofold (9.2% to 19.2%; p < 0.001). There was a 50.8% decrease in overall in-hospital mortality between Cohort 1 and Cohort 2 (p < 0.001). Conclusions This study indicated the potential beneficial effect of universal health coverage (UHC) in improving cardiovascular healthcare by providing more accessible treatment. It can provide evidence to urge the Indonesian government and other low- and middle-income nations dealing with cardiovascular health challenges to adopt and prioritize UHC.